The Great Moderation of Grain Price Volatility: Market Integration vs. Climate Change, Germany, 1650–1790 - Hakon Albers; Ulrich Pfister; Martin Uebele (European Historical Economics Society (EHES), 2018)
In Malthusian economies, crop shortages could be a matter of life and death. The development of regional and national markets for grain held the potential to provide insurance against the demographic consequences of local crop failure. Weather shocks that are reflected in price data, however, entail a measurement problem for market integration studies, which we solve against the background of the end of the Little Ice Age. We exemplify our method to measure price convergence and the link from grain prices to mortality for Germany based on a new data set of rye prices for 15 cities in 1650–1790. We find price convergence in North-Western Germany as well as along major rivers. In addition, a substantial moderation of aggregate rye price volatility occurred, which we link theoretically to increased arbitrage. Mortality was positively related to the aggregate rye price and thus, the decline of rye price volatility decreased the risk to die of hunger in pre-industrial Germany.
Keywords: N13; N53; O13; 330; Market integration; price volatility; agriculture; weather; climate; unified growth theory